PROMISCUITY AMONG MILLENNIAL TEENAGERS AND ITS SOLUTION FROM THE PERSPECTIVE OF HADITH - Saputra, Doni; Almunadi, Almunadi; Nadhiran, Hedhri (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
Adolescence is a phase of human life where curiosity always surrounds thoughts and feelings. This curiosity lies a huge desire, which is especially about promiscuity. In the context of today's society, teenagers and promiscuity are two things that cannot be separated. In fact, instead of having free sex which is detrimental, Islam has shown a solution to overcome this, namely by getting married or fasting as a means to avoid heinous acts which are detrimental. This research uses qualitative methods by the library research category, with primary data from the hadith books of al-Jami' Ash-Shahih li Al-Bukhori and Muslim. The research concludes that promiscuity among millennial teenagers currently appears to no longer be a taboo subject due to the unstoppable rapid flow of social media information and a lack of self-awareness and parental supervision. However, Rasulullah SAW as a role model has given instructions for the people to overcome this by marriage. If this is not possible, then it is recommended to fast (Shawm). Fasting in this case can be contextualized in the current era by doing positive things that can protect oneself from bad desires.